Efficacy and safety of musculoskeletal manipulations in elderly population with musculoskeletal disorders: a systematic review - Alessandro Mauro; Donatella Bagagiolo; Michela Persiani; Luca Cicchitti; Luca Vismara; Irene Bruini; Francesca Buffone (BMJ Open)
Introduction Non-pharmacological interventions, including musculoskeletal manipulations (MMs), have been proven effective for musculoskeletal disorders.Objectives To evaluate if MMs, including osteopathic manipulation and chiropractic care, are effective to improve quality of life, pain intensity and function in older adults with musculoskeletal disorders.Design Systematic review.Data sources A systematic search was conducted on MEDLINE/PubMed, EMBASE, Scopus, Web of Science, CINAHL, Cochrane Library, from database inception up to 2 January 2025.Eligibility criteria Randomised controlled trials, controlled non-randomised trials and open label trials evaluating the efficacy and safety of MM such as osteopathic manipulation, chiropractic manipulation, myofascial release, craniosacral therapy, as monotherapy or adjunctive therapies in older people (age ≥65 years) with musculoskeletal disorders. The main outcomes included pain intensity, functionality and quality of life. Additionally, other related outcomes were considered, such as medical use duration, mood, mobility, motion, strength and endurance. Finally, we considered any adverse events.Data extraction and synthesis Selection and data extraction were performed independently by two authors. The effect estimates for each study were performed using Review Manager V.5.14. Continuous outcomes were analysed using the mean difference (95% CI). The methodological quality of the included studies was assessed using the Cochrane Risk of Bias tool 2 (RoB 2). No meta-analysis was performed.Results Five parallel randomised controlled trials were included, with a total sample size of 676 participants (41.6% women with a mean age of 77.3 years): 34 with chronic pain, 265 with neck pain and 377 with low back pain. MMs were not effective in patients with chronic pain, neither in pain intensity nor in functionality. For neck pain, considering the main outcomes, only in one of the two studies was there a statistically significant improvement in neck pain intensity only at week 12 for spinal manipulative treatment (SMT)+home exercise (HE) compared with HE alone (ES=–0.90 (95% CI –1.46 to –0.34); p=0.002). For low back pain, SMT+HE showed a statistically significant reduction in pain at 12 weeks compared with HE (ES=−0.79 (95% CI −1.39 to –0.19) p=0.010. For neck pain and low back pain, no statistically significant improvement in functional status and quality of life was observed with MM compared with any control group. RoB 2 showed a high risk of bias in three studies and some concerns in the others. At the domain level, the lowest risk was observed in the randomisation process (80% with some concerns). All five studies reported adverse events, none of which were serious.Conclusions This review provides limited and inconclusive evidence about MM to improve quality of life, pain management and functional status in older adults with musculoskeletal disorders. However, MM appears to be generally safe and well-tolerated.PROSPERO registration number CRD42023473203.